Artificial Intelligence in sports journalism: a study in Brazil and Portugal - Canavilhas, João (2023)
Artificial Intelligence has reached journalism in different phases of the news production process, from the identification of news trends to data processing or the automatic production of texts, among others. Its potential manifests itself especially when there is a large amount of data, something that sections such as sports and economy can offer. Of the two options, in this work we chose sports journalism and, thus, we sought to know and understand how newspapers, radios, TV's and digital native products in Brazil and Portugal have been related to Artificial Intelligence. To achieve the proposed objectives, we sent a survey to the heads of several media in both countries with questions that helped us to realize that editors and managers know the contribution that AI can offer to their newsrooms. Among other results obtained, we highlight that the use of AI in the Brazilian media is more present than in Portugal, but there is a convergence in its uses and in the difficulties for further development: lack of economic resources and low knowledge about the potential of AI. Among the reasons for the use of technology, the objective of making the work of journalists more efficient and saving time in production stand out. It is concluded that Portuguese and Brazilian sports media editors are aware of the potential of AI, but right now economic and professional difficulties are the main adversary to its implementation in newsrooms.